Nephrotoxicopathology properties of gold and iron oxide nanoparticles with Perchloric Acid & SiPEG as radiographic contrast media - Mohamed, Muhamad Idham; Mohammad, Mohd Khairul Amran; Abdul Razak, Hairil Rashmizal; Md Saad, Wan Mazlina (UPM Press, 2021)
Introduction: Exponential research and development of nanotechnology has lead to its implementation in medical line such as radiographic imaging. In current practice, iodine is clinically used as a contrast media in radiographic analyses. However, contraindication of iodine to kidney in clinical practice warrants for a better contrast enhancer with lower toxicity. Gold nanoparticles (GNPs) and Iron Oxide nanoparticles (IONPs) have been proposed as potential iodine’s substitute due to their novel biocompatibility. Methods: In accordance with technology-driven toxicity impact, an animal modeling study has been conducted to assess the nephrotoxicopathology of GNPs and IONPs with Perchloric Acid and SiPEG by biochemical study, in-depth tissue examination by histopathology, apoptosis, and ultrastructural observation, and molecular analysis by Comet Assay. Results: Renal function test (RFT) revealed significant alteration in iodine group compared to nanoparticles and negative control group (p<0.05). Reactive oxygen species (ROS) generation and lipid peroxidation (MDA) levels demonstrated significant reduction in both nanoparticles’ groups compared to iodine (p<0.05), suggesting for lower oxidative stress induction. Morphological aberration demonstrated by histology and ultrastructural evaluation (TEM) showed a distortion in kidney tissues and nucleus’ structure of iodine-administered group as compared to control and nanoparticles’ group. Apoptosis detection by TUNEL assay for GNPs and IONPs group also revealed a significant reduction in apoptotic cells compared to iodine group. Comet assay revealed significant reduction in DNA damaging effect of GNPs and IONPs group compared to iodine group. Conclusion: The present study may postulate that GNPs and IONPs show better contrast enhancer properties with lesser toxic properties than iodine.